PENGARUH KEPEMIMPINAN, KOMPENSASI DAN IKLIM ORGANISASI TERHADAP MOTIVASI KERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA PADANG PANJANG - Zulheri Zul; Yasri Hasim (Program Studi Magister Manajemen, 2014)
The aim of this research is to investigate the influence of leadership toward the compensation & organizational climate, the effect of the compensation on the organizational climate, and the impact of the compensation and organizational climate on the work motivation. Population of this study is all employees (62 persons) in Dinas Perhubungan Komunikasi & Informatika of Padang Panjang Region. Based of slovin formula 54 employees were selected as the respondence, is path analysis was used answer the research problem. This study proved that the leadership ha significant influences toward the compensation & organizational climate, The compensation significantly effected on organizational climate and compensation & organizational climate significantly influenced the work motivation. Keywords: Leadership, Compensation, Organizational Climate, Work Motivation